Construction of Direct Z-Scheme Photocatalyst by Mg1.2Ti1.8O5 and g-C3N4 Nanosheets toward Photocatalytic H2 Production and Disinfection - Sijia Gu; Dan Zhang; Shirong Luo; Heng Yang (International Journal of Photoenergy)
Exploring a novel and efficient photocatalyst is the key research goal to relieve energy and environmental issues. Herein, Z-scheme heterojunction composites were successfully fabricated by loading g-C3N4 nanosheets (CN) on the surface of Mg1.2Ti1.8O5 nanoflakes (MT) through a simple sol-gel method followed by the calcination method. The crystalline phase, morphologies, specific surface area, and optical and electrochemical performance of the samples were characterized by X-ray diffraction (XRD), field emission scanning electron microscopy (FE-SEM), energy-disperse X-ray spectroscopy (EDS), Brunauer-Emmett-Teller (BET), diffuse reflectance spectroscopy (DRS), and electrochemical measurements. Considering the suitable band structures of the components, the photocatalytic performance was evaluated by photocatalytic H2O splitting and photocatalytic inactivation of Escherichia coli (E. coli). Among the samples, MT/CN-10 (the molar percentage of melamine to as-obtained Mg-Ti gel was 10%) shows superior photocatalytic performance, which the average H2 production rate was 3.57 and 7.24 times higher than those of MT and CN alone. Additionally, the efficiency of inactivating Escherichia coli (E. coli) over MT/CN-10 was 1.95 and 2.06 times higher as compared to pure MT and CN, respectively. The enhancement of the photocatalytic performance was attributed to the advantages of the extremely negative conduction band (CB) of CN and the extremely positive valence band (VB) of MT, the enhanced light absorption, and more efficient photogenerated charge carrier separation.